2014
DOI: 10.1590/0103-6440201302439
|View full text |Cite
|
Sign up to set email alerts
|

Toothache, Associated Factors, and Its Impact on Oral Health-Related Quality of Life (OHRQoL) in Preschool Children

Abstract: The aim of this study was to assess the prevalence of toothache, associated factors and impact of this condition on the Child Oral Health Related Quality of Life (COHRQoL) in preschoolers. The study was carried out in Santa Maria, Brazil, during the National Children's Vaccination Day, and 534 children aged 0 to 5 years were included. Clinical variables included dental caries and dental trauma. A questionnaire was responded by the parents and provided information about several socioeconomic indicators, dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
102
4
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(139 citation statements)
references
References 20 publications
13
102
4
20
Order By: Relevance
“…The negative impact of dental caries on children's QL includes increased experience of pain sensation, difficulty chewing or sleeping, decreased appetite, weight loss, behavioral changes (irritability and low self‐esteem), frequent absences from school and/or reduction in school performance . Thus, the high prevalence of dental caries is significantly associated with high CPQ scores in children 8‐10 years of age …”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of dental caries on children's QL includes increased experience of pain sensation, difficulty chewing or sleeping, decreased appetite, weight loss, behavioral changes (irritability and low self‐esteem), frequent absences from school and/or reduction in school performance . Thus, the high prevalence of dental caries is significantly associated with high CPQ scores in children 8‐10 years of age …”
Section: Discussionmentioning
confidence: 99%
“…Although no symptoms can be found at the early stage of dental caries, discomfort or pain can occur when the lesion progresses into dentin or involves the dental pulp . Untreated ECC might cause difficulties in sleeping and eating, and possibly affect children's growth and development . Studies have reported that children who suffer from cavitated dentin caries have been found to have lower body weight and height, compared with those without dental caries .…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons for dental caries to affect the quality of life is painful sensition [16][17] . Toothache leads to limitations in the oral functioning and emotional state of the child 18 , causing difficulty to relax and problems in school performance 19 , as well as difficulty sleeping 16 .…”
mentioning
confidence: 99%